Wokół rzeczy ostatecznych. Obyczaje funeralne sowieckich elit partyjnych - Jasiewicz, Krzysztof (Studia Polityczne, 2023)
Soviet funeral practices for members of the state elite are built on two factors. They use the achievements of antiquity and the Bible, and depend on the position of the deceased at the time of their death. On the one hand, ‘elite’ refers to the highest-ranked representatives of the Soviet authorities (primarily the first secretaries of the party and marshals of the army and sometimes very meritorious activists). The custom of mummification, which was taken from antiquity and the Bible, was used for Lenin and Stalin. However, what was done with the bodies of these two most important Soviets was actually thanatopraxis, which involves replacing blood in the bloodstream immediately after death by introducing in its place a fluid with a strictly protected chemical composition that preserves the corpse from the inside. Piłsudski’s body was also subjected to thanatopraxis after death. This method is still used today by families of various magnates and of important mafia people. The second factor is the evaluation of a given person by successors. When speaking of special burial sites, except for the two aforementioned figures, others were buried next to Lenin’s mausoleum (formerly, from 1953 to 1956, Lenin’s and Stalin’s, then only Lenin’s until modern times). All the first/general secretaries of the Communist Party are buried there, except Nikita Khrushchev. He did not deserve a proper burial as he had thrown Stalin’s body out of the mausoleum into an earthen grave and revealed a veil of state secrets in a secret report on the cult of personality and its disastrous consequences on the party elite, which at that time had only been bestowed by Stalin. He was buried at the Novodevichy Cemetery. It is also a very prestigious burial place for many prominent Soviets. There are also several other Moscow necropolises, which served as the resting place of equally distinguished comrades as space at the Novodevichy Cemetery was reduced.